Getting Its Feet on the Ground: Elucidating Paralouatta’s Semi-Terrestriality Using the Virtual Morpho-Functional Toolbox - Püschel, Thomas A.; Marcé-Nogué, Jordi; Gladman, Justin; Patel, Biren A.; Almécija, Sergio; Sellers, William I. (Frontiers in Earth Science, 2020)
Currently, there are no extant platyrrhine primates living in the main Caribbean islands. However, the fossil record of this island region has provided spectacular findings of different platyrrhines that were part of a diverse radiation showing exceptionally unusual morphologies. Among these, the Cuban genus Paralouatta represents some of the most enigmatic primates ever discovered in the Greater Antilles. Some researchers have argued that Paralouatta’s post-cranium shows evidence of semi-terrestriality, a locomotor adaptation that is unusual, if not unique, in platyrrhine evolutionary history. Whether or not Paralouatta was truly semi-terrestrial remains uncertain, however, due to a lack of more sophisticated functional analyses on its morphology. Using novel virtual morpho-functional tools on a comparative sample of 3D talar models of diverse anthropoids representing different substrate preferences, this study aims to further assess whether Paralouatta corresponds to a semi-terrestrial species or not. Specifically, finite-element analysis and geometric morphometrics were used to empirically assess biomechanical performance and shape, respectively, and then several machine-learning (ML) algorithms were trained using both the biomechanical and morphometric data to clarify the substrate preference of the fossil specimens. The ML algorithms categorized the Paralouatta fossils as either arboreal or as species commonly active on both ground and in trees. These mixed results are suggestive of some level of semi-terrestriality, thus representing the only known example of this locomotor behavior in platyrrhine evolutionary history.